Article Review: Running Dictation Gme - rizka hayati rizka hayati (Journal of English Education, Literature and Linguistics, 2020)
This article describes the result of article review about running dictation game. This research aims to review how do teachers use running dictation game to improve students’ in English skills based on article. This research is library research. The techniques of collecting research data are primary data and secondary data. The result of the research is the researcher concludes from four articles. The first article title is “Running Dictation as an Effective Technique on The Teaching Writing Skill” from that article the researcher can conclude Running dictation technique motivates the students to have wider ideas to write their text. The second article title is “Peningkatan Keterampilan Berbicara Doubt Expression melalui Model Pembelajaran Running Dictation Menggunakan Media TEGAR pada Siswa Kelas IX-6 MTs Negeri 1 Ternate Tahun Ajaran 2016/2017.” The result of this research indicate an increase in doubt expression in speaking skill. The third article title is “The use of Running Dictation Technique to Improve Students’ Listening Skill” the conclusion from this article is it is found that Running Dictation technique can improve students’ listening skill. The fourth article is “The Effectiveness of Reading Comprehension Using Running Dictation Technique at The Eight Grade Students of SMP Muhammadiyah 2 Kediri” this article explained The researcher can conclude that Running Dictation Technique is effective in reading comprehension. Based on four articles explanation above, it can conclude that using running dictation game can improve four English skills. There are speaking, writing, listening and reading. Keywords: Article Review, Running Dictation Game